Answer:
-3/4 degree Fahrenheit
Step-by-step explanation:
The temperature is decreasing by 3/16 each day
We write that as -3/16
There are 4 days in which we are measuring
Total temperature change = rate of change* number of days
=-3/16 * 4
= -12/16
We can simplify this by dividing the top and bottom by 4
-12/4 =3
16/4 =4
=12/16 = -3/4
Answer:
-3/4 degree Fahrenheit
Step-by-step explanation:
If the tempature is changing every day by -3/16 degree fahrenhiet, the change in the tempature after 4 days is -3/4 degree Fahrenheit.
Which equation can be used to solve for b?
8 Ft
b = (8)tan(30°)
b=tan(30°)
b = (8)sin(30)
b =8/ sin(30)
Answer:
Answer is
b = (8)tan(30°) - first choice
Step-by-step explanation:
Steps:
tan 30=b/8
b= 8tan30°
Option (a) is correct, b = (8)tan(30°) is the equation which can be used to solve for b
What is Trigonometry?Trigonometry is a branch of mathematics that studies relationships between side lengths and angles of triangles
In a right angle triangle the three sides are represented by the letters a, b and c .
a represents the side adjacent with given angle .
b represents the side opposite to the given angle.
c represents the hypotenuse of the triangle .
Check the attached image for clear picture of the right angle triangle with angle 30 degrees .
Using the trigonometric ratio we can write the ratio as
b/a = tan 30
Multiplying both sides by a , we get
b= a tan 30
since a=8 so
b =8 tan (30)
Hence, b = (8)tan(30°) is the equation which can be used to solve for b
To learn more on trigonometry click:
https://brainly.com/question/25122835
#SPJ5
What is the slope of the function (-2,8) (-1,2)(0,-4)(1,-10)(2,-16)
Answer:
-6
Step-by-step explanation:
To find the slope, plug any two of your points into the slope formula.
I'll use your first two; (-2, 8) and (-1, 2).
[tex]\frac{y2-y1}{x2-x1}[/tex]
Your y1 term is 8, your y2 term is 2.
Your x1 term is -2, your x2 term is -1.
[tex]\frac{2-8}{-1-(-2)} \\\\\frac{-6}{-1+2} \\\\\frac{-6}{1} \\\\-6[/tex]
Your slope is -6.
Answer:
The slope is [tex]\huge \boxed{-6}[/tex].
Step-by-step explanation:
Slope formula:
[tex]\displaystyle \frac{Y_2-Y_1}{X_2-X_1}=\frac{RISE}{RUN}[/tex]
[tex]\displaystyle \frac{2-8}{(-1)-(-2)}=\frac{-6}{1}=-6[/tex]
Therefore, the slope is -6, and the correct answer is -6.
choose the correct ordered pair.
X+ y = 3
y=8
A. (5,8)
B. (11,8)
C. (-5,8)
D. (-11,8)
Answer: C
Step-by-step explanation:
plug in y=8 to
x+y=3
x+8=3
x=-5
There is no need to look at the other answer choices since they do not have x equaling to -5.
So,
[tex]x+y=3\Rightarrow y=3-x[/tex]
Then,
[tex]8=3-x\Rightarrow x=-5[/tex]
The ordered pair is therefore,
[tex]C(-5,8)[/tex]
Hope this helps.
r3t40
In Zoe's garden, the ratio of the number of green peppers to the number of red peppers is 3:4. If there number are 60 red peppers, how many green peppers are in Zoe's garden? F. 54. G. 55. H. 48. I. 45.
Answer:
I. 45.
Step-by-step explanation:
3 green peppers g green peppers
-------------------- = --------------------------
4 red peppers 60 red peppers
Using cross products
3 * 60 = 4 * g
180 = 4g
Divide each side by 4
180/4 =4g/4
45 = g
There are 45 green peppers
| 4.75 - 2.3
as a fraction simply
Answer:
2.45 or 2 9/20
Step-by-step explanation
What is the midpoint of the segment shown below?
The answer to the question is A
Select the algebraic equation that correctly represents the given sentence, and solve the equation. If 4 is subtracted from twice a number, the result is 12 less than the number. A. 2x – 4 = x + 12 x = 16 B. 2x + 4 = x – 12 x = –16 C. 2x + 4 = x + 12 x = 8 D. 2x – 4 = x – 12 x = –8
Answer:
Divide and express 2.7/1.1 to the nearest tenth.
Step-by-step explanation:
If AB is an angle bisector of CAD, what is the value of x?
Answer:
x = 8
Step-by-step explanation:
Angle bisector splits an angle into two equal angles
4x + 1 = 33
4x = 33 - 1
4x = 32
x = 32/4
x = 8
Answer:
x=8
Step-by-step explanation:
If AB is a bisector, that means angles CAB and BAD are equal
<CAB = <BAD
33 = 4x+1
Subtract 1 from each side
33-1 = 4x+1-1
32 = 4x
Divide each side by 4
32/4 = 4x/4
8 =x
What is the mean of the data set?
108, 305. 252, 113, 191
Answer:
193.8
Step-by-step explanation:
The 'mean' of a set is the set's average.
To find the average, add the terms together and divide by the number of terms.
[tex]108+305+252+113+191\\413+252+113+191\\665+113+191\\778+191\\969[/tex]
Divide by your number of terms (5).
[tex]\frac{969}{5} =193.8[/tex]
Answer:
193.8
Step-by-step explanation:
You add up all of the numers and get 969. Then you have to divide by the amount of numbers there are so divide by 5 and get 193.8
(xy + 9y + 2) and (xy – 3)
Answer:
x^2y^2 +9xy^2-xy-27y-6
Step-by-step explanation:
(xy+9y+2) (xy-3)
Each term of second bracket will be multiplied with the terms of first bracket
= xy(xy+9y+2) -3(xy+9y+2)
= x^2y^2+9xy^2+2xy-3xy-27y-6
=x^2y^2+9xy^2-xy-27y-6
Find Malcolm’s debt-to-income ratio if his monthly expenses are $975 and his monthly salary is $1200.
Question 8 options:
a) 1.23
b) 0.795
c) 0.75
d) 0.8125
Answer: D. 0.8125
Step-by-step explanation: His expenses is $975, and his salary is $1200. Divide the expenses by the salary to find the debt-to-income ratio.
975/1200 = 0.8125
The debt-to-income ratio is 0.8125.
Answer:
d) 0.8125
Step-by-step explanation:
Malcolm’s debt-to-income ratio is 0.8125 if his monthly expenses are $975 and his monthly salary is $1200.
All you have to do is divide monthly expenses by the monthly salary.
975 ÷ 1200 = 0.8125
Given f(x) =x-7 and g(x)= x^2 find f(g(-1))
Answer:
-6
Step-by-step explanation:
f(g(-1)) means we need to find g(-1) and then plug that result into f(x).
So let's start:
g(-1) means to replace the input variable in g(x)=x^2 with -1.
So we replace x with -1.
g(-1)=(-1)^2
g(-1)=1
Now that we have g(-1) can be replaced with 1, we can further evaluate f(g(-1)).
So let's do that:
f(g(-1))
f(1)=1-7 ; I replaced the x in f(x)=x-7 with 1 to find f(1).
f(1)=-6
----
Putting altogether
f(g(-1))=f((-1)^2)=f(1)=1-7=-6.
Answer:
f(g(-1)) = -6
Step-by-step explanation:
* Lets explain how to solve the problem
- The problem is about the composite function
- A composite function is a function that depends on another function.
- A composite function is created when one function is substituted into
another function.
- Ex: f(g(x)) is the composite function that is formed when g(x) is
substituted for x in f(x)
* lets solve the problem
∵ f(x) = x - 7
∵ g(x) = x²
- We want to find f(g(-1))
* At first lets find g(-1) by substitute x in the function g(x) by -1
∵ g(x) = x²
∵ x = -1
∴ g(-1) = (-1)² = 1
* Now we want to find f(g(-1)), then we will substitute x in f(x) by
the value of g(-1)
∵ g(-1) = 1
∵ f(x) = x - 7
∴ f(g(-1)) = f(1)
∵ f(1) = 1 - 7 = -6
∴ f(g(-1)) = -6
What is the following product 3 square root 16 x7 times3 square root 12 x9
Answer:
[tex]4x^5\sqrt[3]{3x}[/tex]
Step-by-step explanation:
The product will be written as:
[tex]\sqrt[3]{16x^7}*\sqrt[3]{12x^9}[/tex]
As both the radicals have same root 3 so,
[tex]= \sqrt[3]{16x^7 * 12x^9}[/tex]
The powers of x will be added as the base is same
[tex]=\sqrt[3]{16*12 * x^{(7+9)}}\\=\sqrt[3]{192x^{16}}\\[/tex]
We have to break the terms so that the powers can be written as a multiple of 3
[tex]=\sqrt[3]{64*3*x^{15}*x}\\ =\sqrt[3]{(4^3)*3*(x^{3*5})*x}\\ Applying\ cube\ root\\= 4x^5\sqrt[3]{3x}[/tex]
PLZ HELP!! Select the correct answer.
Which rational equation fits the graph?
Answer:
C
Step-by-step explanation:
When we set the numerator equal to 0 and solve for x, that value is the horizontal asymptote (a line the graph come towards, but never crosses).
Looking at the graph, the horizontal asymptote is x = 2, so which one of the 4 functions has a horizontal asymptote of 2? Let's check.
A) 2x - 1 = 0
x = 1/2
B) same, x = 1/2
C) 2x -4 = 0
x = 2
D) same as A,B, x = 1/2
As we can see, option C has the right horizontal asymptote and A,B,D are eliminated. So answer is C.
PLS HELP, math is my weakest subject and my teachers made it worse.
Answer:
The correct answer to this problem is the final option, angle BTA is congruent to angle ATC.
Step-by-step explanation:
To solve this problem, we first have to unpack the meaning of the given information. First, let's remember that CPCTC means that corresponding parts of congruent triangles are congruent. This means that the same parts of two different triangles that are stated to be congruent (the same) are thus also congruent (the same).
In this case, triangle BAT and triangle CAT are stated to be congruent. This means that line segment BA and CA are congruent, angles BAT and CAT are congruent, and more because of CPCTC (explained above).
The correct answer to this problem is the final option, angle BTA is congruent to angle ATC. We can figure this out simply by looking at the triangle names. Angle ATC is the same as angle CTA (the letters are just in reverse order). From the congruence statement, we can tell that BTA and CTA are congruent angles due to the fact that triangle BAT and CAT are congruent using CPCTC. Looking at the figure, this makes sense because these two angles appear to be the same measure.
Also, we can eliminate the other answer choices, since they are not corresponding parts of the two triangles (the line segments and angles do not represent two congruent pieces of the triangle - they are not matched up correctly).
Hope this helps!
Which point would map onto itself after a reflection across the line y= -x
A) -4,-4
B) -4,0
C) 0,-4
D) 4,-4
Answer:
d
Step-by-step explanation:
Answer:
D. (4, -4).
Step-by-step explanation:
y = -x is a line that has a negative slope of -1 ( rising to the left) and passing through the origin. It makes an angle of 45 degrees with the x-axis.
So, for example the point ( 0,1 )will map onto( -1 , 0).
Any point which maps on to itself across this line will have to lie on the line.
If x = 4 y = -x = -4.
Can you guys help me with question
first off, let's notice something, the graph seems a bit misleading, since the height of the nut is 0.5 cm, whilst the side of the base is 0.6 cm, however in the picture 0.5 appears longer. That said
1)
the volume of the nut itself is simply the volume of a hexagonal prism, which will just be the product of the area of the hexagon and the height.
[tex]\bf \textit{area of a regular polygon}\\\\ A=\cfrac{1}{2}ap~~ \begin{cases} a=apothem\\ p=perimeter\\ \cline{1-1} a=0.5\\ p=\stackrel{0.6\times 6}{3.6} \end{cases}\implies A=\cfrac{(0.5)(3.6)}{2}\implies A=0.9 \\\\[-0.35em] ~\dotfill\\\\ \stackrel{\textit{volume of the hexagonal prism}}{\stackrel{\textit{hexagon's area}}{(0.9)}~~\stackrel{\textit{height}}{(0.5)}\implies 0.45}[/tex]
2)
[tex]\bf \textit{volume of a cylinder}\\\\ V=\pi r^2 h~~ \begin{cases} r=radius\\ h=height\\ \cline{1-1} r=0.4\\ h=0.5 \end{cases}\implies V=\pi (0.4)^2(0.5)\implies V\approx 0.25[/tex]
3)
well, the composite figure is just a hexagonal nut with a cylindrical hole, so if we simply get the volume of the prism and subtract the volume of the cylindrical hole, what's leftover, is the volume of the nut alone without the hole.
[tex]\bf \stackrel{\textit{from 1)}}{0.45}~~-~~\stackrel{\textit{from 2)}}{0.25}\implies 0.20[/tex]
4)
in short, dividing the mass of 3.03 by our result from 3)
3.03 ÷ 0.2 = 1.515.
Can someone please help me ??
Answer:
$1.80
Step-by-step explanation:
Based on the ratio shown in the double number line, the cost for 1 pound of avocados is $1.80.
5 pounds = 9$
9 divided by 5 = 1.8$/pound
Answer:
$1.80
Step-by-step explanation:
Note this:
5 lbs of avocado/$9
So, how much for 1 lb?
Remember units!!! They REALLY are important!!
1_lb_ x $9____ = (1 x 9)/5 = 1.8
5 lbs
**where are the numbers in our conversion coming from? Our notes!
We must now convert our answer to $'s, so $1.80 is our answer!
what is the solution to 3x + 5 > or equal to 7
Answer:
[tex]x \geq\frac{2}{3}[/tex]
Step-by-step explanation:
The question is [tex]3x+5 \geq 7[/tex]
We simply take the numbers to one side and variables to one side and solve via algebra (shown below):
[tex]3x+5 \geq 7\\3x \geq 7-5\\3x \geq 2\\x \geq\frac{2}{3}[/tex]
This range of values is the solutions of the inequality.
If an image of a triangle is congruent to the pre-image, what is the scale factor of the dilation?
0.1
1/2
1
10
If an image of a triangle is congruent to the pre-image, the scale factor of the dilation is 1
How to determine the scale factorFrom the question, we understand that the images are congruent
This means that, the shape is not dilated.
Instead, the shape is translated, reflected or rotated.
When a shape is not dilated, the scale factor is 1
Hence, the scale factor of the dilation is 1
Read more about dilation at:
https://brainly.com/question/10253650
Which of the following shows the solution set of the inequality
3x-5>_19?
Answer:
A
Step-by-step explanation:
3x-5≥19
Add 5 to each side
3x-5+5≥19+5
3x ≥ 24
Divide each side by 3
3x/3 ≥24/3
x ≥8
Since this is greater than or equal to there is a closed circle at 8
greater than means the line goes to the right
A teacher surveyed her class to find out how many texts the students send in a week. She created this box plot to show the data
Zane is washing cars to help pay for a school trip. He gets paid $8 for every car he washes and made a total of $64 on Saturday. Write an equation to show how many cars Zane washed on Saturday.
A)8 − x = 64
B)64x = 8
C)8 + x = 64
D)8x = 64
Answer:
The correct option is D.
Step-by-step explanation:
Let the number of cars Zane washed on Saturday be x.
It is given that he gets paid $8 for every car he washes and made a total of $64 on Saturday.
We need to write an equation to show how many cars Zane washed on Saturday.
If he get $8 for one car, then the total amount he get for x cars is
Total amount = 8x
He made a total of $64 on Saturday, so
[tex]8x=64[/tex]
The required equation is 8x=64.Therefore the correct option is D.
The polynomial f(x) is written in factored form:
f(x) = (x − 6)(x + 5)(x − 9)
What are the zeros of the polynomial function?
x = 6, x = −5, x = 9
x = 6, x = 5, x = 9
x = −6, x = 5, x = −9
x = −6, x = 6, x = −5, x= 5, x = −9, x = 9
Answer:
x = 6, x = -5, x = 9
if f(x)=(x-6)(x+5)(x-9)
Step-by-step explanation:
The zeros of a polynomial in factored form can be found by setting the polynomial equal to zero and then realizing if a product is zero, then at least one of it's factors is zero.
So we have the zero's are the x's that satisfy
(x-6)(x+5)(x-9)=0.
We just need to solve three equations:
x-6=0
This can be solved by adding 6 on both sides: x=6
x+5=0
This can be solved by subtracting 5 on both sides: x=-5
x-9=0
This can be solved by adding 9 on both sides: x=9
The solutions are in { 6,-5,9 }.
Answer:
x = 6, x = -5, x = 9
Step-by-step explanation:
If the polynomial f(x) is written in factored form, f(x) = (x − 6)(x + 5)(x − 9), the zeros of the polynomial function are x = 6, x = -5, x = 9.
x-6=0 x = 6
x+5=0 x = -5
x-9=0 x = 9
Therefore, x = 6, x = -5, x = 9 would be the correct answer.
can you please solve this
Let the length = x and the width = y
For the length of fence we have x +x + y = 48 = 2x +y = 48
Rewrite as y = 48 - 2x
For the area we have x * y = 254
Replace y in the are equation:
x * 48 -2x = 254
Simplify the left side:
48x - 2x^2 = 254
Subtract 254 from both sides:
48x - 2x^2 - 254 = 0
Using the quadratic formula solve for x:
a = -2, b = 48 and c = -254
x = -48 + 4√17/-4
x = 16.123 m.
The length = x = 16.123 meters.
The width = 48 - (16.123*2) = 15.754 meters
Rounding to the nearest centimeter:
Length = 16.1 ( 16 meters and 1 cm)
Width = 15.8 ( 15 meters and 8 cm)
−2x+30>4x+12-2x+30>4x+12
Express the set using interval notation.
Answer:
[-∞, 3)
Step-by-step explanation:
We are given the following inequality which we are to express as a set using the interval notation:
[tex] - 2 x + 3 0 > 4 x + 1 2 [/tex]
Rearranging the inequality by adding the like terms together to get:
[tex] - 2 x - 4 x < 1 2 - 3 0 [/tex]
[tex] - 6 x < - 1 8 [/tex]
[tex]x<\frac{-18}{-6}[/tex]
[tex]x<3[/tex]
Since the values of [tex]x[/tex] are lesser than [tex]3[/tex] so we can express this in interval notation as:
[-∞, 3)
Evaluate in 5.
A.) 0.62
B.) 0.70
C.) 1.61
D.) 1.95
Answer:
option C) 1.61Step-by-step explanation:
The question is to evaluate the natural logarithm of 5. Natural logarithms are logarithms with base e.
e is the irrational number equal to 2.71828182845904523536028747 ... (being irrational the decimals do not end and do not have a repetition period).
Logarithms are evaluated using tables or scientific calculators.
ln (5) = 1.6094379... it is also an irrational number, so it has infinite decimals with no repetition period.
So, rounding to two decimal numbers, ln (5) = 1.61, which is the option C).
Answer:c
Step-by-step explanation:test
Write the ordered pair that represents MP. Then find the magnitude of MP.
M(-19,4), P(4,0)
a. (23– 4): 1545 units
c. (23; - 4): 545 units
b. (-15, 4): 1545 units
d. • (-15, 4): 545 units
Answer:
(23,-4):[tex]\sqrt{545}[/tex] units
Step-by-step explanation:
We are given that M(-19,4)and P(4,0)
We have to find the ordered pair that represents MP and find the magnitude of MP.
MP=P-M
MP=(4,0)-(-19,4)=(4+19,0-4)
MP=(23,-4)
Magnitude of MP=[tex]\sqrt{(23)^2+(-4)^2}[/tex]
Magnitude of MP=[tex]\sqrt{529+16}[/tex]
Magnitude of MP=[tex]\sqrt{545}[/tex] units
Hence, .option c is true.
Answer:c.(23,-4):[tex]\sqrt{545}[/tex] units
Answer:
A 2021
Step-by-step explanation:
The coordinates of the vertices of a polygon are (−2, −2) , (−2, 3) , (2, 4) , (3, 1) , and (0, −2) .
What is the perimeter of the polygon?
Enter your answer as a decimal, rounded to the nearest tenth of a unit, in the box.
units
Step-by-step explanation:
i have answered ur question
The Perimeter of the given polygon can be calculated using the distance formula for each of its sides. The calculated distances are added to give a total perimeter of approximately 18.5 units.
Explanation:The Perimeter of a polygon is calculated by adding the lengths of all its sides. Here, we need to calculate the distance between each pair of points, which gives the length of the sides of the polygon.
The distance between two points (x1, y1) and (x2, y2) is given by the formula sqrt((x2-x1)² + (y2-y1)²) .
To find the Perimeter of the polygon, we calculate the distances between each pair of vertices and then add them up:
Adding these distances, we get a perimeter of approximately 5 + 4.1 + 3.2 + 4.2 + 2 = 18.5 units, rounded to the nearest tenth of a unit.
Learn more about the Perimeter of a polygon here:https://brainly.com/question/15387363
#SPJ3
the point-slope form of the equation below that represents the line that passes through the points (−3, 2) and (2, 1).
Answer:
[tex]\large\boxed{for\ (-3,\ 2):\ y-2=-\dfrac{1}{5}(x+3)}\\\boxed{for\ (2,\ 1):\ y-1=-\dfrac{1}{5}(x-2)}[/tex]
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
========================================
We have the points (-3, 2) and (2, 1).
Substitute:
[tex]m=\dfrac{1-2}{2-(-3)}=\dfrac{-1}{5}=-\dfrac{1}{5}[/tex]
for (-3, 2)
[tex]y-2=-\dfrac{1}{5}(x-(-3))\\\\y-2=-\dfrac{1}{5}(x+3)[/tex]
for (2, 1)
[tex]y-1=-\dfrac{1}{5}(x-2)[/tex]